1982
DOI: 10.1016/s0022-5347(17)53516-8
|View full text |Cite
|
Sign up to set email alerts
|

Immunology of Pyelonephritis in the Primate Model

Abstract: Ascending acute pyelonephritis was produced in monkeys by infusion of bacteria through a ureteral catheter to the point of intrarenal reflux. This led to a significant inflammatory response with death of renal tubular cells in the area of the tubular granulocytes and bacteria. We gave superoxide dismutase, and found that the inflammatory response was decreased and fewer tubular cells were killed. Ultrastructural change was also decreased in tubular cells adjoining phagocytosing neutrophils. This suggests that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…In fact, both macrophages and neutrophils may have liberated a variety of cytokines (tumor necrosis factor and interleukins), metabolites of arachidonic acid, and noxious inflammatory mediators such as oxygen radicals and lysosomal enzymes during the process of phagocytosis, which may have accounted for the deleterious effects to kidney cells. While inhibition of acute suppuration by cyclophosphamide-induced neutropenia (9) or antioxidant therapy with radical scavengers such as superoxide dismutase (37) and even complement depletion with cobra venom factor (38) have all been reported to reduce kidney damage after infection, the present study reports a major protective role for a leukotriene inhibitor in pyelonephritis.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In fact, both macrophages and neutrophils may have liberated a variety of cytokines (tumor necrosis factor and interleukins), metabolites of arachidonic acid, and noxious inflammatory mediators such as oxygen radicals and lysosomal enzymes during the process of phagocytosis, which may have accounted for the deleterious effects to kidney cells. While inhibition of acute suppuration by cyclophosphamide-induced neutropenia (9) or antioxidant therapy with radical scavengers such as superoxide dismutase (37) and even complement depletion with cobra venom factor (38) have all been reported to reduce kidney damage after infection, the present study reports a major protective role for a leukotriene inhibitor in pyelonephritis.…”
Section: Discussionmentioning
confidence: 53%
“…For example (17,37), the presence of bacteria in the renal parenchyma during pyelonephritis induces a marked local cellular and humoral response. Inflammatory cells such as polymorphonuclear cells (PMNs) migrate into the interstitium under chemotactic stimuli and then release free oxygen radicals (02 -, OH, and H202) and lysosomal enzymes into their environment.…”
mentioning
confidence: 99%
“…However, from our data it is impossible to ascertain whether the SOD activities per cell are really changing during the cell cycle, because we are determing the activitĂ©s in SOD relative to total pro tein and not the SOD content per cell as a process of time. Similar criticism as to the analysis of SOD activity has already been reported [6], The half-life of SOD in the blood is less than 6 min, but SOD is excreted by the kid neys [15]. Subsequently any effect of SOD is probably influenced by urinary or renal SOD activity.…”
Section: Totalmentioning
confidence: 60%
“…Roberts et al [4] also reported that SOD reduced the damage to renal tubular cells in an acute pyelonephritis model, suggesting that superoxide leads to a loss of renal tissue and function, and so-called chronic pyelonephritis.…”
Section: Suppression O F Enhanced Renal Scarring By Peg-sodmentioning
confidence: 97%
“…Phorbol myristate ace tate (PMA) has been reported to stimulate the PMNs into releasing superoxide via an activation of protein kinase C [4], In this study, we examined the effects of PMA on renal scarring following infection. …”
Section: Introductionmentioning
confidence: 99%